DASAR-DASAR DAN TUJUAN PENDIDIKAN ISLAM - M, Munadira (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic education plays a crucial role in shaping individuals who are intellectually, spiritually, and morally balanced. This study aims to identify the foundational principles and objectives of Islamic education, which serve as essential pillars in its development. Using a library research method, the study reveals six primary foundations of Islamic education: the Qur'an and Hadith, philosophical foundations, formal juridical foundations, psychological foundations, sociological foundations, and axiological foundations. Furthermore, the objectives of Islamic education are analyzed through six perspectives: Qur'an and Hadith, philosophical, juridical, psychological, sociological, and axiological perspectives. The findings indicate that Islamic education aims to nurture individuals with faith, piety, and extensive knowledge while preparing them for life in both this world and the hereafter. In conclusion, Islamic education plays a strategic role in fostering individuals capable of fulfilling their responsibilities as stewards on Earth and contributing positively to society.